The modern concept of the extension of active longevity - geroprotectors and evidence-based medicine - Karnaukh, Ella; Piniaeva, V. (My University, 2016)
The main drugs with geroprotection effect proven during the multi-stage clinical trials used in world medical practice for the extension of active longevity. The role of the drugs in the support structure of the global concept of of physical, mental, emotional and social health preservation at the maximum lifespan and disability. The main drugs illustrates of modern geroprotectors classification on their mechanisms of action
Современная концепция продления активного долголетия - геропротекторы с позиции доказательной медицины
Keywords: geroprotectors; life expectancy; healthy life